Maximizing Downlink Non-Orthogonal Multiple Access System Capacity by A Hybrid User Pairing Strategy - Zhong, Dinghui; Deng, Danhao; Wang, Chaowei; Wang, Weidong (2021 IEEE/CIC International Conference on Communications in China (ICCC), 2021)
Non-Orthogonal Multiple Access (NOMA) is considered as a promising technique candidate for the next-generation of cellular networks. An effective user pairing strategy in a cluster can increase the capacity of downlink NOMA system consistently. In this paper, we propose a novel hybrid user pairing to process a case where the number of far users in a cell is larger than the number of near users. Conventional NOMA divides users into multiple groups according to their channel gains, however, there will be a large amount of far users left when the pairing of near users is completed in this scenario. In such case, we allow multiple far users being paired with one near user to optimally utilize the spectrum of far users in the NOMA system, and multiple far users share the same bandwidth. We have compared the proposed algorithm with conventional NOMA, OMA and some algorithms proposed in other papers, simulation results show that the proposed algorithm can significantly increase the system capacity. The superiority of the proposed algorithm is also analyzed from the perspective of user fairness.